Information literacy as a mechanism of epistemic negotiation in the utilization of artificial intelligence: A case study at the INSTIPER Yogyakarta Library - Helmi Afroda; Ayuna Meilawati (Daluang: Journal of Library and Information Science, 2026)
Purpose. This study aims to examine the role of information literacy as a mechanism of epistemic negotiation in the utilization of artificial intelligence (AI) within academic environments, with a case study conducted at the INSTIPER Yogyakarta Library. Methodology. This study employed a qualitative descriptive method with a case study approach. Data were collected through semi-structured in-depth interviews with lecturers and students, as well as document analysis of academic policies and information literacy materials. Data were analyzed using descriptive thematic analysis through transcription, coding, theme categorization, and interpretation of meaning. Results and discussion. The findings reveal that information literacy functions as a mechanism of epistemic negotiation that enables users to critically evaluate, verify, and interpret AI-generated information. Information literacy also guides the ethical use of AI while reducing excessive dependence, plagiarism, and technological misuse in academic activities. Furthermore, the INSTIPER Yogyakarta Library plays a strategic role as a policy mediator, facilitator of AI literacy, and promoter of a critical and responsible academic culture. These findings indicate that information literacy in the AI era extends beyond technical information retrieval skills toward a reflective capacity to assess the legitimacy, credibility, and validity of knowledge generated or mediated by AI. Conclusions. Information literacy plays a crucial role in strengthening critical and responsible engagement with AI in academic environments. The findings provide a reference for university libraries in developing information literacy programs and AI usage policies oriented toward strengthening academic integrity, critical evaluation, and responsible knowledge practices.